The Relationship Of Giving Mpasi To Babies Under 6 Months And The Incident Of Constipation And Diarrhea In Krajan Hamlet, Kalisat Village, Rembang District Pasuruan District - Puji Kumalasari, Eri; Devy Putri Nursanti; Asruria Sani Fajriah (Journal for Quality in Public Health, 2023)
Infant morbidity and mortality in Indonesia is quite high, the most common cases are disorders of the digestive system, including constipation and diarrhea. The aim of this study was to analyze the relationship between giving complementary foods to babies under 6 months of age with the incidence of constipation and diarrhea in Krajan Hamlet, Kalisat Village, Rembang District, Pasuruan Regency. The research design uses a correlational analytical design with a cross sectional approach. The number of samples in this study was 32 respondents. Sampling in this study used simple random sampling technique. Data collection using questionnaires. Data analysis used the chi square statistical test with a significance level of α = 0.05. Based on the research results, of the 32 respondents, the majority of respondents were given MP ASI, namely 20 respondents (62.5%), the majority of respondents did not experience constipation, namely 25 respondents (78.1%), the majority of respondents did not experience diarrhea, namely as many as 19 respondents (59.4%). The results of the chi square statistical test obtained a P value < α 0.05 (0.020 < 0.05), so H1 was accepted or Ho was rejected, meaning that there was a relationship between giving MP ASI to babies under 6 months of age and the incidence of constipation in Krajan Hamlet, Kalisat Village, District. Rembang, Pasuruan Regency and there is a relationship between giving MP ASI to babies under 6 months of age with the incidence of diarrhea in Krajan Hamlet, Kalisat Village, Rembang District, Pasuruan Regency with a P value < α 0.05 (0.000 < 0.05). The conclusion of this study is that the incidence of constipation and diarrhea is influenced by giving MP-ASI to babies aged less than 6 months so it is hoped that mothers of babies will increase their knowledge about giving proper MΡ-ASI to prevent constipation and diarrhea.